Future of Health Care Delivery in Iran, Opportunities and Threats - R Majdzadeh; N Rostamigooran; H Esmailzadeh; F Rajabi; L Doshmangir (Tehran University of Medical Sciences, 2013)
Background: The aim of this study was to determine the impact of important social and technological trends on health care delivery, in the context of developing "Iran's Health System Reform Plan by 2025".Methods: A detailed review of the national and international literature was done to identify the main trends affecting health system. To collect the experts' opinions about important trends and their impact on health care delivery, Focus Group Discussions (FGDs) and semi-structured in-depth interviews techniques were used. The study was based on the STEEP model. Final results were approved in an expert's panel session.Results: The important social and technological trends, affecting health system in Iran in the next 15 years are demographic transition, epidemiologic transition, increasing bio-environmental pollution, increasing slums, increasing private sector partnership in health care delivery, moving toward knowledge-based society, development of information and communication technology, increasing use of high technologies in health system, and development of traditional and alternative medicine. The opportunities and threats resulting from the above mentioned trends were also assessed in this study.Conclusion: Increasing healthcare cost due tosome trends like demographic and epidemiologic transition and uncontrolled increase in using new technologies in health care is one of the most important threats that the health system will be facing. The opportunities that advancement in technology and moving toward knowledge-based society create are important and should not be ignored.